Stock conditions and status of blue swimming crab (Portunus pelagicus) in Demak water area, the northern coast of Central Java - Aisyah Nur Nabila; Am Azbas Taurusman; Budy Wiryawan; Mochammad Riyanto (Faculty of Marine and Fisheries, Universitas Syiah Kuala, 2022)
Blue swimming crab (Portunus pelagicus) is the dominant catch in Betahwalang, Demak, and the most important export fish commodity, particularly to USA. The high demand for this crab has been promoting an excessive fishing effort, causing a decrease in the crab's natural stock. This study aims to investigate the biological condition of P. pelagicus on the northern coast of Central Java and assess the crab stock exploitation status in this study area. Carapace width, body weight, Gonad Maturity Stages (GMS), and sex of crab samples were collected from the fishers and collectors landing sites or meeting points. This study employs a simple random sampling technique with no replacement. This study revealed that the maximum carapace width of female crabs was 56-164 mm, and the estimated carapace width at first maturity (Lm) was 98.2 mm. The relationships between carapace width and body weight between male and female crabs indicated positive and negative allometric growth patterns. During this assessment, the P. pelagicus stock indicated an 'over-exploited’ status, with an LB-SPR parameter of 19 percent and an exploitation rate (E) of 0.66. Management measures such as minimum legal size, reduced effort, and open-close areas and seasons should be implemented to achieve sustainable use of the crab fishery.Keywords:Blue swimming crabFishing gearDemak watersCarapace lengthSpawning potential ratio